Translation and validation of the Chinese version of the acceptance and action questionnaire for cancer in patients with advanced lung cancer - Huiyuan Li; Marques Shek Nam Ng; Xiaohuan Jin; Cho Lee Wong (Elsevier, 2023)
Objective: This study aimed to examine the reliability and validity of the Chinese version of the Acceptance and Action Questionnaire for Cancer (C-AAQ-Cancer) in patients with advanced lung cancer. Methods: In Phase I, the AAQ-Cancer was translated from English to Chinese. In Phase II, an expert panel was invited to examine the content validity of the translated instrument, and pilot testing was performed. In Phase III, a total of 200 patients with advanced lung cancer from a university-affiliated hospital in central China were recruited to test the construct validity of the translated AAQ-Cancer using exploratory factor analysis, and reliability was assessed based on internal consistency and test-retest reliability. Results: The semantic equivalence and content validity index of the C-AAQ-Cancer were satisfactory. Exploratory factor analysis indicated that the C-AAQ-Cancer contained the following five subscales: cancer concerns, blunting, blame, distancing, and behavioral disengagement. These subscales explain 68.28% of the total variance. The Cronbach's α coefficient of the scale was 0.87, and the test-retest reliability was 0.839. Conclusions: This study evaluated the psychometric properties of the C-AAQ-Cancer. The findings support the reliability and validity of this instrument in evaluating experiential avoidance or acceptance levels in patients with advanced lung cancer.